1986
DOI: 10.1001/jama.1986.03370100093024
|View full text |Cite
|
Sign up to set email alerts
|

Noncontraceptive Hormones and Rheumatoid Arthritis in Perimenopausal and Postmenopausal Women

Abstract: The use of noncontraceptive hormones before onset of joint disease was compared between 490 perimenopausal and postmenopausal women with rheumatoid arthritis and a control group of 659 women with soft-tissue rheumatologic disorders and/or osteoarthritis. Both groups were sampled randomly from the attendees of five rheumatologic clinics. A negative association was found between the onset of rheumatoid arthritis and the previous use of noncontraceptive hormones (odds ratio, 0.32; 95% confidence interval, 0.16 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Most of the previous studies have not observed an association [ 12 , 13 , 19 26 ]. Our results are in accordance with a report by Vandenbroucke et al [ 29 ] where current use of substitution hormones was associated with a decreased risk of RA. Our results are also in line with a previous case-control study, where a decreased risk of RA among current users of estrogen plus progestin was found and, as in our study, no association for current users of estrogen only was observed [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Most of the previous studies have not observed an association [ 12 , 13 , 19 26 ]. Our results are in accordance with a report by Vandenbroucke et al [ 29 ] where current use of substitution hormones was associated with a decreased risk of RA. Our results are also in line with a previous case-control study, where a decreased risk of RA among current users of estrogen plus progestin was found and, as in our study, no association for current users of estrogen only was observed [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…The use of postmenopausal hormone (PMH) therapy for menopause related symptoms in relation to RA risk has been explored in several studies, most of them showing no association [ 12 , 13 , 19 26 ] while a few have reported an increased [ 27 ] or decreased risk of developing RA [ 28 , 29 ]. One report has indicated that the use of PMH among women carrying the HLA-DRB1 shared epitope (SE) alleles may protect against the development of criterium-defined RA in a population of women with early undifferentiated arthritis, and that this prevention is associated with a reduction of antibodies to citrullinated peptides (ACPA) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flowchart of literature inclusion and exclusion. We identified 47 publications for full-text evaluation, of which 30 publications were further excluded because they did not fulfill the inclusion criteria (ie, conference abstracts,3442 meta-analyses/reviews,5058 letters to editor/comments,59 cross-sectional studies,29,30 providing insufficient data,28 involving the same study population or overlapped data,8,31–33 involving family cases,13,17 reporting the relationship between noncontraceptive hormones and RA among perimenopausal and postmenopausal women,11 and using OCs users with less than one patient as reference9). Therefore, our meta-analysis was based on 17 publications, including 12 case-control and five cohort studies published between 1982 and 2010 4,7,10,12,1416,1827.…”
Section: Resultsmentioning
confidence: 99%
“…67,68 Although no data in MS have been reported about the long-term effects of oral contraception, in RA the effects of oral contraception have been debated. No definite conclusion could be drawn, since a beneficial effect has been documented in some earlier studies, 69,70 while in others oral contraception had no effect. 71,72 This may reflect the reduced amount of oestrogen in more recent oral contraceptives and the use of synthetically modified oestrogen.…”
Section: Oestrogenmentioning
confidence: 89%